2017
DOI: 10.13057/biofar/f150204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water stress on phenolic content and antioxidant activity of African nightshades

Abstract: Okello OP, Gweyi JPO, Nawiri Mp, Musila W. 2017. Effects of water stress on phenolic contents and antioxidant activity of African nightshades. Biofarmasi J Nat Prod Biochem 15: 79-95. This study aimed at mapping out the distribution of different African Nightshade species in Siaya and Kisii Counties of Kenya and to determine water stress effect on total antioxidant capacity and total phenolic content of two selected African nightshade namely, giant nightshade (Solanum scabrum) and black nightshade (Solanum vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
2
5
3
Order By: Relevance
“…In addition, results suggested that coumaric acid and quercetin are potent antioxidants with proven therapeutic efficacy 81 , 82 . Our experiment is also in consistent with other researches (Jakovljević et al 84 , Okello et al 83 , Prinsi et al 31 ). On a large scale, high phenolics content are directly related to higher resistance of plants to pests and diseases, and thus a precise regulation of N supplementation could present agroecosystem related advantages by reducing pesticide usage in agriculture.…”
Section: Resultssupporting
confidence: 94%
“…In addition, results suggested that coumaric acid and quercetin are potent antioxidants with proven therapeutic efficacy 81 , 82 . Our experiment is also in consistent with other researches (Jakovljević et al 84 , Okello et al 83 , Prinsi et al 31 ). On a large scale, high phenolics content are directly related to higher resistance of plants to pests and diseases, and thus a precise regulation of N supplementation could present agroecosystem related advantages by reducing pesticide usage in agriculture.…”
Section: Resultssupporting
confidence: 94%
“…Notably, the leaf area yielded by Ogembo Oyaro et al [65] ranged from 120 to 130 cm 2 on two different African nightshades grown in a greenhouse is in accordance with the results of the present study. On the contrary, the results of leaf area (304.45 cm 2 ) obtained by Okello et al [64] are higher than leaf area of 121.7 cm 2 obtained from the current study under the greenhouse condition. Leaf area development is directly related to the yield of African nightshades since the edible part is the leaf [64].…”
Section: Discussioncontrasting
confidence: 91%
“…However, in our study, low-chlorophyll content observed in greenhouse-grown plants may be linked to fertiliser deficiency and high humidity and temperatures [63]. A study by Okello et al [64] reported that Solanum scabrum had a higher leaf area of 304.45 cm 2 under greenhouse cultivation subjected to the different levels of irrigation water stress. Notably, the leaf area yielded by Ogembo Oyaro et al [65] ranged from 120 to 130 cm 2 on two different African nightshades grown in a greenhouse is in accordance with the results of the present study.…”
Section: Discussioncontrasting
confidence: 48%
“…Phenolic compounds, which are secondary metabolites, perform various defense functions in plant organs during stress. Studies conducted by Okello et al (2017) showed that Solanum scabrum and Solanum villosum plants respond differently to water deficiency. As a result of stress, phenolic compounds accumulate more in the roots of S. scabrum and the leaves of S. villosum.…”
Section: Resultsmentioning
confidence: 99%
“…The phenols accumulated in the roots act as osmolytes, participate in the maintenance of turgor in the root cells and increase the osmotic potential. In the leaves, phenolic compounds participate in the defense of enzymes under stress, protection of the structure and integrity of the membrane, and utilization of reactive oxygen species (Okello et al, 2017).…”
Section: Resultsmentioning
confidence: 99%